It’s a matter of microbes: a perspective on the microbiological aspects of micro- and nanoplastics in human health - Stunnenberg, Melissa; de Roda Husman, Ana Maria (Frontiers in Nanotechnology, 2024)
Micro- and nanoplastics (MNPs) are everywhere: in the air we breathe, in our food and in virtually every type of water. Currently, it is unknown whether, and to what extent, these MNPs are hazardous to human health. Identifying risks of physical and chemical aspects of MNPs has gained a lot of attention over the last few years, and efforts have been made to quantify these risks. In our opinion, the momentum delivered by these efforts should be used to highlight the relevance of including another important aspect of MNPs: their associated microbes. Although more and more studies describe MNP-associated microbes, the interplay between physical, chemical and microbiological aspects are lacking. Hazard identification parameters describing this interplay are crucial to risk assessment strategies, yet the majority of effort has been directed towards optimizing human exposure parameters. Here, we address the importance of including microbiological aspects of MNPs in the risk assessment of MNPs. Physical and chemical aspects of MNPs impact the diversity and abundance of microbes and antibiotic resistance genes (ARGs). In turn, environmental factors (e.g., UV radiation, antibiotics) may impact the microbial composition directly, or indirectly by impacting physical or chemical MNP aspects. Future efforts should be directed towards investigating this interplay in order to determine the effects of these dynamic outcomes on human health. We believe that elucidating these pieces of the puzzle is needed to ultimately perform a more holistic risk assessment of MNPs on human health.